Pengaruh Penerapan Model Pembelajaran Partisipasi Terhadap Hasil Belajar Siswa Pada Bidang Studi IPS Terpadu Pada Kelas VII di Raudlatul Wathoni NW Taman Sari - Suhaibatul Aslamiah (Pendidikan Al-Gafari, 2024)
One of the problems of education in Indonesia that is widely discussed is the low quality of education which is reflected in the low average learning outcomes. Another problem is that the approach to learning is still too dominated by the role of teachers. This study aimed to improve the learning outcomes of social studies of class VIII students at MTs Raudlatul Wathoni NW Taman Sari on identifying market forms in community economic activities. This study is a class experiment study which was carried out only 3 times in two classes, namely class VIIIA (experimental class) and class VIIB (control class). Student learning outcome data were collected through an evaluation test given at the end of the meeting. The results of the study showed that there was an increase in student learning outcomes, namely in the experimental class the average value was 70.13, and in the control class with an average value of 66.25. Based on these results, overall this study can be said to be successful because there is a difference between the learning outcomes of the experimental class and the learning outcomes of the control class. At the end of the study, the purpose of the study had been achieved where student learning outcomes had met the requirements for achievement. namely the average class value increases from each cycle and the classical learning completion of at least 85% of students getting a score of >60 has been achieved. So it can be concluded that the implementation of the participatory learning model can improve the social studies learning outcomes of MTs Raudlatul Wathoni NW Taman Sari students.